2013
DOI: 10.5935/1984-6835.20130018
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic Amines: A Public Health Problem

Abstract: Biogenic amines (BA) are toxic low molecular weight organic bases with aliphatic, aromatic or heterocyclic structures that can be found in several foods and are mainly produced by microbial decarboxylation of amino acids. The consumption of food containing large amounts of BA can result in allergic reactions, characterized by difficulties in breathing, rash, vomiting and hypertension. BA are also known as possible precursors of carcinogens such as Nnitrosamines. They are frequently found in high concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The effect of the commercial fish gelatin protein hydrolysate on rainbow trout (Oncorhynchus mykiss) fillet quality control measures to prevent contamination by these substances have focused on inhibiting microbial growth and reducing decarboxylase activity (Cardozo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The effect of the commercial fish gelatin protein hydrolysate on rainbow trout (Oncorhynchus mykiss) fillet quality control measures to prevent contamination by these substances have focused on inhibiting microbial growth and reducing decarboxylase activity (Cardozo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Animal-origin foods are naturally rich in free amino acids and, therefore, they are susceptible to contamination by BAs. In fish and meat, BA concentration increases postmortem due to the high quantity of proteolytic enzymes present in the intestinal tract, combined with the rapid autolysis process (Cardozo et al 2013).…”
Section: Humansmentioning
confidence: 99%
“…People with respiratory disorder, heart problems or vitamin B 12 deficiency are particularly sensitive. Individuals with stomach problems usually have lower intestinal oxidative activity and they are also an at-risk group (Cardozo et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that once the biogenic amine is formed, it is difficult to remove (Cardozo, Lima, França, & Lima, 2013). It is critical that the formation mechanism for biogenic amine in wheat Qu should be found and blocked.…”
Section: Biogenic Amine In Wheat Qumentioning
confidence: 99%